SUCCESSFUL TREATMENT OF DISSECTION OF THE INTERNAL CAROTID ARTERY - V. V. Zelenin (Issledovaniâ i Praktika v Medicine, 2018)
The clinical observation of a successful treatment of a young patient with intima dissection of the internal carotid artery and thrombosis of the lumen of the internal carotid artery and the middle cerebral artery of traumatic genesis is presented. Injury of the internal carotid artery occurred with a large physical load of a rotational nature. Fracture of the styloid process caused a dissection of the internal carotid artery with its thrombosis on the extracranial level and the development of ischemic stroke in the basin of this artery. In an emergency order, a complex of diagnostics was performed-CT CT, CT angiography. The first stage was performed thrombextracion from the internal carotid artery and the middle cerebral artery by the X-ray endovascular method. To fix the intima in the internal carotid artery in the area of her injury we stented her. Complete revascularization was achieved in the basin of the internal carotid artery with almost complete regression of neurologic symptoms. The patient returned to work. The use of x-ray endovascular mini-invasive technologies, thrombus extraction and stenting in the next few hours after the development of AVCC allowed to achieve a good near and distant clinical result.